1996
DOI: 10.1037/0097-7403.22.1.76
|View full text |Cite
|
Sign up to set email alerts
|

Quantity-based interference and symbolic representations in chimpanzees (Pan troglodytes).

Abstract: Five chimpanzees with training in counting and numerical skills selected between 2 arrays of different amounts of candy or 2 Arabic numerals. A reversed reinforcement contingency was in effect, in which the selected array was removed and the subject received the nonselected candies (or the number of candies represented by the nonselected Arabic numeral). Animals were unable to maximize reward by selecting the smaller array when candies were used as array elements. When Arabic numerals were substituted for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
236
7
2

Year Published

1999
1999
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(260 citation statements)
references
References 31 publications
15
236
7
2
Order By: Relevance
“…For example, although chimpanzees readily learn an object match-to-sample task (given A as standard, choose alternative A rather than B), they have great difficulty learning a relational match-to-sample task (given AA as standard, choose alternative BB rather than CD) (Oden et al 2001;Premack 1983) -a task that human children can master before five years of age (Christie and Gentner 2007). Interestingly, these highly intelligent animals can learn and use numbers up to around 8 (Boysen et al 1996). For example, chimpanzees in Boysen's study could point to the correct Arabic numeral when given a set of items, and could point to a set of objects when given a numeric symbol.…”
Section: Relational Ability Across Speciesmentioning
confidence: 99%
“…For example, although chimpanzees readily learn an object match-to-sample task (given A as standard, choose alternative A rather than B), they have great difficulty learning a relational match-to-sample task (given AA as standard, choose alternative BB rather than CD) (Oden et al 2001;Premack 1983) -a task that human children can master before five years of age (Christie and Gentner 2007). Interestingly, these highly intelligent animals can learn and use numbers up to around 8 (Boysen et al 1996). For example, chimpanzees in Boysen's study could point to the correct Arabic numeral when given a set of items, and could point to a set of objects when given a numeric symbol.…”
Section: Relational Ability Across Speciesmentioning
confidence: 99%
“…In an often cited study by Boysen, Berntson, Hannan, and Cacioppo (1996) a chimpanzee was trained on a reverse contingency task. The chimpanzee was offered a choice between two plates, both of which had candy but one always had more pieces than the other.…”
Section: Primatesmentioning
confidence: 99%
“…Does the reverse reward task test for "self control"? Initially, studies on impulse control were mainly performed with humans (Mischel et al 1989;Russell et al 1991) and primates (Boysen and Berntson 1995;Boysen et al 1996;Silberberg and Fujita 1996;Kralik et al 2002;Genty et al 2004). Some authors have suggested that success in the reverse reward task may be interpreted as a form of "self control" thereby implying that in order to solve the task, some "awareness of self" needs to be involved (e.g.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…In some species that failed to choose the non-preferred reward in order to obtain the preferred one, cues such as Arabic numerals for chimpanzees and colour cues for cottontop tamarins associated with the two quantities of food enabled the species to succeed (Boysen and Berntson 1995;Kralik et al 2002). DiVerences in performance when testing the subjects with food only or with Arabic numerals have been interpreted to result from a conXict between an associative disposition to select the smaller reward in order to obtain the large one and the intrinsic features of the food reward, which could be removed by using symbols (Boysen et al 1996;Boysen et al 1999). Also, in a diVerent procedure, the so called large-or-none contingency facilitated subsequent success in the reverse reward contingency.…”
Section: Introductionmentioning
confidence: 99%